Strategi Peningkatan Profesionalitas Guru Kelas VI Daerah Binaan 3 Kecamatan Batang - Kunarso Kunarso; Iin Purnamasari; Bagus Ardi Saputro (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
This study examines the Strategy for Increasing the Professionalism of Class VI Teachers in the 3rd District of Batang District. The specific objectives of the study were to describe the professionalism of class VI teachers and to describe strategies for increasing the professionalism of class VI teachers in the target areas of 3 Batang District. The usefulness of research is that it can be used as relevant further study material. Discussion of "Strategies for Increasing the Professionalism of Class VI Teachers in the 3 Batang Subdistrict" as an inseparable part of education management which will be discussed in strengthening the validity and reliability in the implementation of school management. The population of this research is the sixth grade teacher in the target area 3, Batang District. A total of 16 people. In this study using primary data. The research method uses a qualitative descriptive approach, because the data collected and the analysis are more qualitative in nature. The results showed that teacher professionalism has four competencies, namely pedagogic competence, personality competence, social competence and professional competence obtained through professional education. The emergence of PAIKEM learning and the success of improving the quality of education and the strategies implemented in improving the Professionalism of Class VI Teachers in the target area of Batang District with Academic Supervision of School Supervisors, Advanced Study of Undergraduate Programs, Courses and Training, Utilization of Professional Journals, Seminars and Discussions. By going through six (6) strategies to improve teacher professionalism, both supported by the policies of the service and institution or the target area, they are able to create teachers who have good professionalism. Suggestions that can be recommended by this research are the need for teachers to always improve their professionalism, in order to carry out their professional duties well in the digital era and the rapid development of science, information and communication.